(untitled) (Communications in Computational Physics, 2014)
Density functional theory combined with the Grüneisen approximation is used to calculate the thermal properties of single-walled boron nanotubes (BNTs). The specific heat and thermal expansion are investigated. The thermal expansion coefficient of the BNT is found to be significantly correlated with tube size and chirality. A remarkable thermal contraction is found at small tube diameters. These results indicate that BNTs would have potential applications in sensors, actuators, and memory materials.